UPAYA MENINGKATKAN HASIL BELAJAR IPS MODEL PEMBELAJARAN CONCEPT ATTAINMENT PADA SISWA KELAS VI.C SDN 09 PASAMAN - Irma Yani (STKIP Pesisir Selatan, 2017)
The purpose of this research is to improve learning outcomes through the use of IPS Learning Model Concept Attainment in VI.C grade students of SDN 09 Pasaman. This study uses classroom action research as much as two cycles. Each cycle consists of four phases: planning, implementation, observation and reflection. The data obtained is qualitative data. From the analysis of Learning Model Concept Attainment had a positive impact in improving student learning outcomes characterized by increased mastery learning students in each cycle, the first cycle (60.00%), the second cycle (88.57%). The conclusion of this study is Learning Model Concept Attainment has a positive influence, that can improve student learning outcomes are indicated with an average response of students stating that students are interested in and are interested in learning Model Concept Attainment so that they become motivated to learn.